The Influence of Foreign Language Accounting Vocabulary Competencies, Accounting Competencies and Computer Competencies on MYOB Learning Outcomes - Murdiyati, Uki; Habibi, Beni; Basukiyatno, Basukiyatno (Department of Economics Education, Faculty of Economics, Universitas Negeri Semarang, 2021)
This study aimed to determine how the influence of mastery of basic accounting vocabulary, accounting competence and computer competence on MYOB accounting computer learning outcomes. The research was included in the quantitative type with the correlational method. The population in this study were students of class XI Accounting at SMK NU 1 Islamiyah Kramat, totalling 115 students in the 2020-2021 academic year. Sampling was carried out by using a random technique using the proportional random sampling method and calculated using the Slovin formula in order to obtain 97 students. This study used primary data sources obtained from tests to measure the level of mastery of English accounting vocabulary, accounting competence and computer competence. Meanwhile, secondary data sources were obtained from several sources which were considered to have relevance to the research. Data analysis used multiple linear regression method. The results of the study, both simultaneously and partially, showed a significant influence between foreign language accounting vocabulary competence, accounting competence and computer competence on MYOB learning outcomes. Suggestions for further research are to examine learning outcomes by presenting intervening variables and linking them with other independent variables.